Pengaruh Kualitas Produk dan Harga Terhadap Keputusan Pembelian (Studi Pada Toko Tas Kawipack di Kota Malang) - Firmansyah, Choyron; Rachma, N.; Primanto, Alfian Budi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract The purpose of this study was determine product quality and price on purchasing decisions partially or simultaneously. This research method uses quantitative research methods and the type of research is purposive sampling. The sample of this study were consumers of Kawipack Bag Stores in Malang City, totaling 55 respondents. To obtain accurate and detailed data, this study used a questionnaire data collection method. The data analysis used is instrument test, normality test, classical assumptions, multiple linear regression analysis, hypothesis testing, and the coefficient of determination using SPSS. The results of this study indicate that product quality and price simultaneously have a significant effect on purchasing decisions at Kawipack Bag Stores in Malang City. Furthermore, partially product quality and price have a positive and significant effect on purchasing decisions at Kawipack Bag Stores in Malang City. Keywords : Product Quality, Price, Purchasing Decisions.